Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1073/pnas.0913986107
|View full text |Cite
|
Sign up to set email alerts
|

Relevant use of Klotho in FGF19 subfamily signaling system in vivo

Abstract: α-Klotho (α-Kl) and its homolog, β-Klotho (β-Kl) are key regulators of mineral homeostasis and bile acid/cholesterol metabolism, respectively. FGF15/ humanFGF19, FGF21, and FGF23, members of the FGF19 subfamily, are believed to act as circulating metabolic regulators. Analyses of functional interactions between α-and β-Kl and FGF19 factors in wild-type, α-kl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
131
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(147 citation statements)
references
References 34 publications
11
131
4
Order By: Relevance
“…In line with these findings, our present study demonstrated an indispensible role of ␤-klotho in FGF21-induced ERK1/2 activation, GLUT1 gene transactivation, and glucose uptake in adipocytes. In contrast, a recent study on ␤-klotho knock-out mice suggests that it is not required for FGF21 signaling pathways leading to the expression of hormone sensitive lipase and AtgI (23). However, whether or not ␤-klotho is essential for FGF21-induced GLUT1 expression and glucose uptake has not been addressed in this study.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…In line with these findings, our present study demonstrated an indispensible role of ␤-klotho in FGF21-induced ERK1/2 activation, GLUT1 gene transactivation, and glucose uptake in adipocytes. In contrast, a recent study on ␤-klotho knock-out mice suggests that it is not required for FGF21 signaling pathways leading to the expression of hormone sensitive lipase and AtgI (23). However, whether or not ␤-klotho is essential for FGF21-induced GLUT1 expression and glucose uptake has not been addressed in this study.…”
Section: Discussioncontrasting
confidence: 43%
“…By contrast, a recent study on ␤-klotho knock-out mice suggests that ␤-klotho may not be essential for FGF21 signaling in adipose tissue (23). However, the latter report did not measure the impact of ␤-klotho deficiency on FGF21-induced glucose uptake in adipocytes.…”
Section: ␤-Klotho Is Required For Fgf21-induced Glut1 Expression and contrasting
confidence: 42%
See 1 more Smart Citation
“…In humans, FGF23 signaling via several FGF receptor (FGFR) subtypes is thought to specifically require KLA, whereas hFGF19 and FGF21 reportedly require KLB (12)(13)(14). But other studies have shown that KLA can also act as a co-receptor for hFGF19 (15).…”
mentioning
confidence: 99%
“…Endocrine FGFs act via receptor tyrosine kinases but also require the presence of a co-receptor, alphaKlotho (KLA) 4 or betaKlotho (KLB) (12). In humans, FGF23 signaling via several FGF receptor (FGFR) subtypes is thought to specifically require KLA, whereas hFGF19 and FGF21 reportedly require KLB (12)(13)(14).…”
mentioning
confidence: 99%